2001
DOI: 10.1046/j.1523-1755.2001.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular cell number in normal subjects and in type 1 diabetic patients

Abstract: The essentially constant glomerular cell density in nondiabetic and diabetic subjects under different circumstances possibly indicates an underlying propensity for the glomerulus to regulate its architecture to maintain a constant number of cells per volume, no matter the size of the glomerulus or the severity of diabetic nephropathy studied in this set of patients. The reductions in podocyte numbers in both younger and older diabetic patients indicate a significant risk for functional abnormalities as diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
251
4
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(273 citation statements)
references
References 27 publications
13
251
4
5
Order By: Relevance
“…In contrast to the decrease in podocyte number, mesangial and glomerular endothelial cell number remained normal. More recently, Steffes et al (110) showed a similar paradigm in patients with type I diabetic nephropathy. Taken together, these important studies showed that a decrease in podocyte number is a significant predictor of disease progression in diabetic nephropathy.…”
Section: Podocyte Number Contributes To Glomerulosclerosismentioning
confidence: 84%
“…In contrast to the decrease in podocyte number, mesangial and glomerular endothelial cell number remained normal. More recently, Steffes et al (110) showed a similar paradigm in patients with type I diabetic nephropathy. Taken together, these important studies showed that a decrease in podocyte number is a significant predictor of disease progression in diabetic nephropathy.…”
Section: Podocyte Number Contributes To Glomerulosclerosismentioning
confidence: 84%
“…The podocyte changes per se may enhance proteinuria and contribute to later damage. Foot process broadening and effacement and a reduction in podocyte number are recognised in diabetes [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Studies in humans and DN animal models reveal podocyte injury, detachment, apoptosis and loss. [4][5][6][7][8] Although some stimuli induce necrosis of podocytes in culture, 9 there is more in vivo evidence for a role of apoptosis in podocyte loss in DN. [10][11][12] More specifically, podocyte apoptosis coincided with the onset of albuminuria and preceded podocytopenia in different mouse models of diabetes.…”
mentioning
confidence: 99%